INFLUENCE OF STANDARD INDICATORS OF SITUATIONAL EFFECTIVENESS IN BASKETBALL, IN BOSNIAN LEAGUE 6 AND REGIONAL BASKETBALL LEAGUE - Vlatko Separović; Meho Alić-Partić; Edin Užičanin (Sport Scientific And Practical Aspects, 2025)
Research was conducted to determine relations among 15 standard indicators of situational effectiveness in basketball and the final score of a basketball game. Data was collected from 50 games in Bosnian League 6, final stage of basketball championships in Bosnia and Herzegovina (league which includes 6 teams who stay in contention for the championship trophy), and 20 games in Regional basketball league (Good Year League) where two teams from Bosnia and Herzegovina took part, “KK Bosna“ from Sarajevo and “HKK Siroki“ from Siroki Brijeg. Results of regression analysis showed that 3 variables have statistically significant influence on the final score of basketball games in Bosnian League, SO and OL on the level of 99%, and IL on the level of 95%. In Regional Basketball League, those variables are S3US, SBUS, SN, IL and OL, on the level of 99%, and S2US on the level of 95%. The difference among obtained results supports the fact of more consistent game in Regional Good Year League.